2013
DOI: 10.1177/0898010113488244
|View full text |Cite
|
Sign up to set email alerts
|

Gardening for the Mental Well-Being of Homeless Women

Abstract: The gardening experience interrupted the participants' negative ruminations, offering stress relief and elements of social inclusion and self-actualization. Gardening is an inexpensive and positive intervention for a population with a high incidence of mental illness and distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 20 publications
2
35
0
1
Order By: Relevance
“…The results showed a positive correlation between the two; however, the study focussed on only one centre with a very small sample size. Grabbe, Ball, and Goldstein () uncover similar findings in their recent study on the benefits of gardening in helping relieve stress in homeless women. Social inclusion is highlighted in Thomas, Gray, and McGinty's () research of homeless people in Australia.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…The results showed a positive correlation between the two; however, the study focussed on only one centre with a very small sample size. Grabbe, Ball, and Goldstein () uncover similar findings in their recent study on the benefits of gardening in helping relieve stress in homeless women. Social inclusion is highlighted in Thomas, Gray, and McGinty's () research of homeless people in Australia.…”
Section: Introductionsupporting
confidence: 52%
“…Grabbe et al (:7) report similar findings in their study of homeless women who found gardening reflected their ‘spirituality and hope’.…”
Section: Results and Analysismentioning
confidence: 72%
“…Besides cultivating and trying to be partially self-sufficient for fruit and vegetables (that are expensive and hard to find now), this could give me psychological benefits. There is an association between home gardening and physical and mental well-being, and this has been demonstrated for various categories of people at risk (Grabbe et al 2013;van Lier et al 2017;John et al 2016;Quick et al 2017). I had a lot of material in my garage, some pipes, shelves, supports, other stuff, and hardware.…”
Section: Introductionmentioning
confidence: 95%
“…Owing to their numerous social, physical and economic benefits, there has been increased interest in the use of community garden (CG) programs to address public health issues in recent times. CGs provide increased access to healthy food options such as fruits, vegetables and organically grown foods, promote physical activity, and improve mental and social well‐being . In both children and adults, increased fruit and vegetable consumption and physical activity have been linked to community gardening .…”
Section: Introductionmentioning
confidence: 99%
“…CGs provide increased access to healthy food options such as fruits, vegetables and organically grown foods, 1 promote physical activity, 2 and improve mental and social well-being. 3,4 In both children and adults, increased fruit and vegetable consumption and physical activity have been linked to community gardening. 5 In fact, it has been observed that gardeners have significantly lower and healthier body mass indexes when compared to those who do not garden.…”
Section: Introductionmentioning
confidence: 99%